Role Stress and Prosocial Service Behavior of Hotel Employees: A Moderated Mediation Model of Job Satisfaction and Social Support - Jin, Yixing; Cheng, Lin; Li, Ying; Wang, Yingda (Frontiers in Psychology, 2021)
Hotel employees’ positive behavior is prone to increase customer satisfaction, and thus, exploring the influencing mechanism of role stress on prosocial service behavior is critical to relieving their stress and improving service quality and hotel performance. This study aims to develop and test a moderated mediation model that links hotel employees’ role stress to prosocial service behavior. Based on the conservation of resources theory and job demands-resources model, this study suggests that the effect of role stress on prosocial service behavior is mediated by the level of job satisfaction, whereas the relationship between role stress and job satisfaction is moderated by social support. Data from 256 hotel employees in China largely support the hypotheses that role stress reduces job satisfaction, and that job dissatisfaction is related to low levels of prosocial service behavior. The data also show that job satisfaction partly mediates the relationship between role stress and prosocial service behavior, and social support weakens the relationship between role stress and job satisfaction. The results can help us understand the role of organization-level resources in the workplace and how role stress and job satisfaction affect prosocial service behavior.